The effect of housing condition on the fur quality and selling price of the pelt in the Finnraccoon - Koistinen, Tarja; Korhonen, Hannu T. (Nordic Association of Agricultural Scientists, NJF, 2017)
The Finnraccoon (Nyctereutes procyonoides ussuriensis) is an important fur animal in Finland. The aim of the present study was to examine whether the housing conditions affect the fur quality and the selling price of the pelt in juvenile Finnraccoons. A total of 152 Finnraccoons were raised from weaning until pelting in four different housing conditions, differing in the cage size, animal density, group size and furnishing of the cage. The length and quality of the fur were evaluated and the selling price was registered. The data were analysed by using the Pearson Chi- square test and Linear Mixed Model (SPSS). The fur quality differed between groups with the poorest quality in the group of four animals housed in an enriched cage. No general difference between males and females was found. No difference between groups was found in the distribution of the pelts into the size categories. The size category and the quality of the fur were the main factors determining the selling price of the pelt. The selling price was higher in pelts of males than in those of females. This difference between males and females appeared only in the Finnraccoons housed in pairs, and not in those housed in groups. When only the auction where the majority of pelts were sold was considered, the selling price of the pelt was higher in females when housed in larger cages instead of small cages and in enriched cages instead of barren cages. In conclusion, the larger cage size and increased complexity of the cage may increase the selling price of pelts in juvenile Finnraccoons, especially in females. Although, the increased cage complexity impairs the quality of the fur, this does not finally affect the selling price of the pelt.